Pengembangan Bahan Ajar IPAS Berbasis Pembelajaran Berbasis Proyek (PjBL) untuk Siswa Kelas VI Sekolah Dasar - Novi Sri Wahyuni; Abna Hidayati; Alwen Bentri; Ramalis Hakim; Suci Fajrina (Postgraduate, University of Mataram, 2025)
This study developed Project-Based Learning (PjBL) instructional materials for Grade-6 IPAS (Integrated Science and Social Studies) using Plomp’s development model. The process followed three consolidated phases: (1) preliminary investigation (curriculum analysis, learner characteristics, learning needs, and review of existing materials); (2) design and construction producing Prototype 1, followed by expert validation of content, language, and media with iterative revision; and (3) test–evaluation–revision, including practicality trials (one-to-one, small group, and field) and descriptive checks of learning outcomes. Mean expert validity was 89.7% on a 0–100% scale. Practicality rose from 78% (one-to-one) to 86% (small group) and 91% (field), placing the materials in the very practical category at field testing (≥90%). During classroom implementation, average student engagement was 87%, and 93% of students met classical mastery on the post-test. The findings indicate high validity ratings and very high practicality for classroom use; outcome data show strong post-test attainment and engagement but do not evidence improvement in the absence of a pre-test or control comparisons. In conclusion, the PjBL-based IPAS materials are feasible for Grade-6 implementation and merit further effectiveness studies using pre–post or comparative designs.